Effectiveness Of 2% And 4% Papain Gels In The Healing Of Venous Ulcers - Ribeiro,Andréa Pinto Leite (2015)
OBJECTIVE To analyze the effectiveness of 2% and 4% papain gels in tissue repair of venous ulcers. METHOD Quasi-experimental study with consecutive sample of 16 patients with 30 venous ulcers treated at the outpatient clinic of a teaching hospital, from April to November in 2011, using a form for clinical assessment of the patient and its lesion. Variables were analyzed by Wilcoxon and McNemar test (p < 0.05). RESULTS Most participants were female; aged between 51 and 59 years; obese; with hypertension. Regarding ulcers, there was an average decrease of 7.9 cm2 (50% of its original size) in 90 days; 20% of the ulcers completely healed within 56.67 days. There was an increase in epithelialization, significant reduction in the slough and edema, improved depth, in the type and amount of exudate (p < 0.0001). CONCLUSION 2% and 4% papain gels were effective in healing venous ulcers.